Molecular and biochemical characterization of LeCRK1, a ripening-associated tomato CDPK-related kinase - Leclercq, Julie (Journal of experimental botany, 2005)
A cDNA clone (LeCRK1), encoding a novel isoform of calcium-dependent protein kinase (CDPK), was isolated by screening a tomato (Lycopersicon esculentum) cDNA library. The protein derived from the full-length sequence indicated that it belongs to the family of CDPK-related kinases (CRKs) and the predicted amino acid sequence shows a modular organization of the protein consisting of different characteristic domains. The kinase domain of LeCRK1 shares a high degree of similarity with the catalytic domain of CDPKs. In contrast to canonical members of the family, LeCRK1 has a degenerate sequence in the C-terminal calmodulin-like domain. LeCRK1 protein was shown to be a functional kinase, but, consistent with the lack of calcium-binding activity, its autophosphorylation activity did not require calcium. LeCRK1 harbours an amphiphilic amino acid region revealed to be a functional calmodulin-binding site by in vitro assay. A putative myristoylation/palmitoylation sequence has been identified at the N-terminus. Expressing an LeCRK1::GFP fusion protein in the protoplast resulted in its targeting to the plasma membrane. Site-directed mutagenesis of critical amino acids of the myristoylation/palmitoylation consensus sites led to the accumulation of the mutated protein in the cytoplasm, suggesting that the native protein is anchored to the plasma membrane by acylated residues. Expression studies revealed significant accumulation of LeCRK1 transcripts during fruit ripening, although transcripts were also detected in stem, leaf, and flower. LeCRK1 mRNA level in leaves was slightly induced by ethylene and salicylic acid, and upon mechanical wounding and cold treatment. It is noteworthy that LeCRK1 mRNAs were undetectable in different tomato-ripening natural mutants such as NR, Rin, and Nor, suggesting a role in the ripening process